YELLOW FEVER: STILL OF CONCERN FOR TRAVELERS OF COLOMBIA? - Alfonso J. Rodriguez-Morales (Asociación Colombiana de Infectología, 2018)
During the last years, the world has witnessed significant yellow fever (YF) epidemics. The one that occurred in Africa, particularly in Angola, during 2016, is a clear example of that. This outbreak included not only locally-transmitted cases in this country, but also 11 imported cases, unprecedently in Asia, specifically in China.3,4 By the way, between Angola and Brazil, there is an increasing number of international travelers arriving to Latin America proceeding from Africa.